Knowledge Enhancement Through Oral Hygiene Learning Videos - Sekar Restuning; Irwan Supriyanto; Nurul Fatikhah (Dental Therapist Journal, 2023)
Learning media is expected to enhance students' interest in learning. This research aims to investigate the impact of instructional videos on the level of oral hygiene knowledge. The research methodology employed in this study is Quasi-Experimental, utilizing a quantitative design with pre-test and post-test approaches. Purposive sampling was employed as the sampling technique. The analysis, conducted using the Paired T-Test, yielded a ρ-value of 0.000 (ρ < 0.05), indicating a significant change in the mean knowledge scores before and after the educational intervention using oral hygiene instructional videos. One alternative approach to dental health education, particularly in tooth brushing, is through the use of videos. Using videos is more effective as it facilitates easier retention and understanding of lessons, transcending reliance on a single sensory input. It is anticipated that future research can develop applications related to accessing oral hygiene instructional videos.